Kult bóstw w państwie nowoasyryjskim (935-609 p.n.e.) w świetle kar finansowych zawartych w dokumentach praktyki prawnej - Zawadzki, Stefan
The Cult of Gods in the Neo-Assyrian Empire 935-609 B.C. in the Light of Financial Penalties as Evidenced in the Legal Documents; Engl. Résumé.